Concordance of Qur'anic polysemy / Ahmad Shehu Abdussalam (book of the month 2009) - Wok, Saodah (Public Relations Office, International Islamic University Malaysia, 2009)
This book helps readers understand the message of the Qur'an by giving precise meaning to some polysemous words found in it. Polysemy is a semantic state of a word that has two or more meanings. Polysemic entries are numbered and arranged in alphabetical order. It also explains the two major approaches in the interpretation of Qur'anic polysemic words. Therefore, it is an essential tool for English-speaking scholars and students of the science of the Qur'an. This is because it helps harmonize various meanings. It brings out certain aspects of the creativity of the Qur'an and it provides linguistic options to the interpretation or translation of the Qur'an.